2011
DOI: 10.1021/la2011937
|View full text |Cite
|
Sign up to set email alerts
|

Real Time Evolution of Liquid Crystalline Nanostructure during the Digestion of Formulation Lipids Using Synchrotron Small-Angle X-ray Scattering

Abstract: The role of the digestion of lipids in facilitating absorption of poorly water-soluble compounds, such as vitamins, is not only an important nutritional issue but is increasingly being recognized as an important determinant in the effectiveness of lipid-based drug formulations. It has been known for some time that lipids often form complex liquid crystalline structures during digestion and that this may impact drug solubilization and absorption. However, until recently we have been unable to detect and charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 30 publications
3
70
1
1
Order By: Relevance
“…At time points 0 min, no liquid crystals are visible, after 30 min a lamellar phase exists, and 90 min hexagonal and lamellar phases co-exist. Reprinted with permission from references (82,89) turn-over for laboratories (93). However, the presence of an oil layer in case of more lipophilic LBDDS required ultracentrifugation for the effective separation of oil, aqueous phase, and pellet.…”
Section: Methods For the Characterisation Of The Drugmentioning
confidence: 99%
“…At time points 0 min, no liquid crystals are visible, after 30 min a lamellar phase exists, and 90 min hexagonal and lamellar phases co-exist. Reprinted with permission from references (82,89) turn-over for laboratories (93). However, the presence of an oil layer in case of more lipophilic LBDDS required ultracentrifugation for the effective separation of oil, aqueous phase, and pellet.…”
Section: Methods For the Characterisation Of The Drugmentioning
confidence: 99%
“…We note that the sequence of phases should be the same independently of the lipase concentration. Recently, Boyd et al demonstrated that it was possible to combine the pH-stat experiment with synchrotron SAXD, although they noted that precautions have to be taken to avoid beam damage [36,37]. As shown in Fig.…”
Section: Progress Of the Lipase Catalyzed Hydrolysis Of Lcnpsmentioning
confidence: 99%
“…In vitro digestion studies were performed using a pH-stat auto titrator (Radiometer, Copenhagen, Denmark), similar to previous reports [8,13,16,17]. Lipids were added to 9 mL of the fasted or fed simulated intestinal fluid in the thermostatted digestion vessel at 37°C at pH 6.5.…”
Section: Lipolysis Model and In Vitro Lipolysismentioning
confidence: 99%
“…In vitro lipolysis models have been developed which aim to better mimic in vivo conditions, and are capable of following the kinetics of digestion by determining the free fatty acid composition of digesting lipid media. Recent studies have utilised this model combined with synchrotron small angle X-ray scattering to enable the changes in nanostructure during lipid digestion to be elucidated in real time [8,9]. However, to the best of our knowledge, no studies exist which compare the two approaches, therefore the purpose of this study was to examine the structures formed at equilibrium, for a series of triglycerides of increasing chain length, compared with the composition and structures formed under non-equilibrium digestion conditions.…”
Section: Introductionmentioning
confidence: 99%